IMPLEMENTASI NILAI-NILAI DEMOKRASI MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Nungki Dwi Abshita Rini (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed to know: (1) The implementation of democratic values, (2) Proponent and obstacle factors, and (3) The solution to cover barrier to the implementation of democratic values through civics education. The type of this study was a descriptive and qualitative research. Data collection techniques used observation, interview, and documentation. Data analysis technique were conducted by reducing, interpreting, and concluding the data. The result of the research shows (1) The implementation of democratic values is done by entering the democratic values in syllabus and lesson plan include tolerance, cooperation, freedom of opinion, mutual respect and confidence. (2) The proponent factors are learning facilities, school culture and school leadership. The obstacle factors arethe decreas of parents proponent, in the circle of society, and difference of person. (3) The solutions areconscious from parents to have pay attention their children, community involvement, and establish good communication with students.